Social Interactions and Institutional Structures that Influence 24-Hour Rooming-in for New Mothers and Newborns in the Hospital Setting. Issue 1 (January 2023) - McRae, Maureen J.; Miraglia, Robbin
Abstract: Purpose: To describe the social interactions and institutional structures that influence the consistent practice of 24-hour rooming-in of new mothers and newborns in the hospital setting. Study Design and Method: Using an institutional ethnographic design, data were gathered via semistructured interviews and on-unit observations. Data were recorded, transcribed, and analyzed for themes. Study interviews were conducted between February 2020 and June 2021. Results: Seven mother–baby nurses were interviewed, and three on-unit observations of 2 hours each were conducted. Analysis of interview data revealed a consensus that Baby-Friendly does not always feel mother-friendly. Three major themes identifying social interactions were identified: the mother as a patient, managing expectations, and inconsistencies in practice. Three themes identified institutional structures that influenced 24-hour rooming-in: rates of induction of labor and cesarean birth, nurse staffing, and monitoring of nursery use. Clinical Implications: Our findings provide insights about how the everyday work of 24-hour rooming-in is organized and experienced by nurses on the mother–baby units at the study hospital. Themes highlight specific social interactions and institutional structures that affect the practice and can be used by hospital leaders and educators to develop targeted interventions for ensuring consistent 24-hour rooming-in. Abstract : Mother-baby nurses shared their experiences with 24 hour rooming-in during postpartum hospitalization. Three themes identifying social interactions that affected rooming in included the mother as patient, managing expectations, and inconsistencies in practice, while three themes as institutional structures that influenced rooming-in were high rates of induction of labor and cesarean birth, inadequate nurse staffing, and lack of monitoring of nursery use. There was a consensus that Baby-Friendly is not always mother-friendly. Nurses offered suggestions for how to improve the rooming in experience for new parents.